Particulate and gaseous emissions from the combustion of different biofuels in a pellet stove. (November 2015) - Vicente, E.D.; Duarte, M.A.; Tarelho, L.A.C.; Nunes, T.F.; Amato, F.; Querol, X.; Colombi, C.; Gianelle, V.; Alves, C.A.
Abstract: Seven fuels (four types of wood pellets and three agro-fuels) were tested in an automatic pellet stove (9.5 kWth ) in order to determine emission factors (EFs) of gaseous compounds, such as carbon monoxide (CO), methane (CH4 ), formaldehyde (HCHO), and total organic carbon (TOC). Particulate matter (PM10 ) EFs and the corresponding chemical compositions for each fuel were also obtained. Samples were analysed for organic carbon (OC) and elemental carbon (EC), anhydrosugars and 57 chemical elements. The fuel type clearly affected the gaseous and particulate emissions. The CO EFs ranged from 90.9 ± 19.3 (pellets type IV) to 1480 ± 125 mg MJ −1 (olive pit). Wood pellets presented the lowest TOC emission factor among all fuels. HCHO and CH4 EFs ranged from 1.01 ± 0.11 to 36.9 ± 6.3 mg MJ −1 and from 0.23 ± 0.03 to 28.7 ± 5.7 mg MJ −1, respectively. Olive pit was the fuel with highest emissions of these volatile organic compounds. The PM10 EFs ranged from 26.6 ± 3.14 to 169 ± 23.6 mg MJ −1 . The lowest PM10 emission factor was found for wood pellets type I (fuel with low ash content), whist the highest was observed during the combustion of an agricultural fuel (olive pit). The OC content of PM10 ranged from 8 wt.% (pellets type III) to 29 wt.% (olive pit). Variable EC particle mass fractions, ranging from 3 wt.% (olive pit) to 47 wt.% (shell of pine nuts), were also observed. The carbonaceous content of particulate matter was lower than that reported previously during the combustion of several wood fuels in traditional woodstoves and fireplaces. Levoglucosan was the most abundant anhydrosugar, comprising 0.02–3.03 wt.% of the particle mass. Mannosan and galactosan were not detected in almost all samples. Elements represented 11–32 wt.% of the PM10 mass emitted, showing great variability depending on the type of biofuel used. Highlights: The highest emission factors were obtained for agro-fuels. Organic carbon contributed no more than 30% of the PM10 mass. Mannosan and galactosan were not detected in almost all samples. Treated wood in pellets generated high contents of Pb, Zn and As in PM10 .